Building Social Enterprises from the Ground Up - Bern, Aleksander; Akin, Deniz (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale)

(untitled) (SFU Canadian Institute for Studies in Publishing, 2025)
The EU-funded Enhancing Social Innovation in Rural Areas (ESIRA) project aims to develop initiatives within the social economy to better include vulnerable groups in rural communities. In Norway, social enterprises are uncommon, and there is no established legal framework for this type of business organization. This situation, combined with high expectations of a traditionally strong welfare state, presents unique challenges for the ESIRA project’s goal of establishing and developing social enterprises and the local social economy. This short article will explore this dilemma based on experiences from the ESIRA project with the aim to offer a nuanced perspective on the interplay between social enterprises and the welfare state.